Condiciones financieras de la Entidad Administradora de Planes de Beneficios de Salud Comfamiliar Huila en el marco del Decreto 2702 de 2014 (solvencia) - Losada Espinosa, Paula Andrea (Universidad Antonio Nariño, 2023)
This document is the product of the investigation that analyed the financial conditions of the Comfamiliar Huila health benefits plan administrator entity within the framework of decree 2702 of 2014 that led to its liquidation in addition to what was stated in the main objetive, the development of this work allowed us to consolidate the knowledge seen during the different semesters of the interpretation and analysis of financial statements. It was deployed under the documentary descriptive approach of financial statements. The conclusions allowed us to understand that in 2019 the company’s crisis denotes an accumulated fiscal déficit of 200 billon pesos, being 7 times e quivalent to the corresponding asset in that period, for the years after the Eps had 260 billon in déficit. The problems in the collection of the portfolio caused the los of liquidity, with this the increase in its obligations affected the exercise of solv ency and acid test.